2015
DOI: 10.1038/srep18533
|View full text |Cite
|
Sign up to set email alerts
|

T cell responses are elicited against Respiratory Syncytial Virus in the absence of signalling through TLRs, RLRs and IL-1R/IL-18R

Abstract: Pattern recognition receptors (PRRs) and cytokine receptors are key players in the initiation of immune responses to infection. PRRs detecting viral RNA, such as toll like receptor (TLR)-3, -7/8, and RIG-I like receptors (RLRs; RIG-I and MDA-5), as well as cytokine receptors such as interleukin 1 receptor (IL-1R), have been implicated in responses to RNA viruses that infect the airways. The latter includes respiratory syncytial virus (RSV), a human pathogen that can cause severe lower respiratory tract infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
(66 reference statements)
2
17
0
Order By: Relevance
“…Second, a MAVS independent mechanism could drive the maturation and antigen presentation capacity of DCs. We have previously shown that mice deficient in MyD88/TRIF and MAVS can mount T cell responses albeit to a reduced level compared to wt mice ( 32 ). In addition, Bhoj et al .…”
Section: Discussionmentioning
confidence: 99%
“…Second, a MAVS independent mechanism could drive the maturation and antigen presentation capacity of DCs. We have previously shown that mice deficient in MyD88/TRIF and MAVS can mount T cell responses albeit to a reduced level compared to wt mice ( 32 ). In addition, Bhoj et al .…”
Section: Discussionmentioning
confidence: 99%
“…Partial deletion of the amino-terminal RNA-binding domain of NS1 from influenza A rescues the production of IL-1β and IL-18 during infection, suggesting that this domain antagonizes the activation of caspase 1 ( 167 ). Intriguingly, Goritzka et al recently showed that while early lung infiltration of immune cells and levels of proinflammatory mediators were abrogated in Myd88 / Trif / Mavs −/− mice (which lack TLR, RLR, and IL-1R signaling), there was no subsequent effect upon the induction of RSV-specific CD8 + T cells ( 168 ). This implies that caspase-1 and TLR7 are essential to the development of adaptive immune responses to influenza virus, while the RIG-I pathway is more important in RSV but that redundant downstream pathways exist to induce cell-mediated immunity even in its absence.…”
Section: Innate Immunity Following Respiratory Virus Infectionmentioning
confidence: 99%
“…This indicates that the interplay between genetics and the environment, including the microbiota and co-infections, will be part of the severity of disease caused by RSV ( Figure 1). Interestingly, even mice genetically lacking the ability to signal via all TLRs and RLRs are able to control RSV infection and mount T cell responses to the virus 63 . This suggests that additional mechanisms for detecting RSV infection exist that can compensate for the lack of PRR signalling.…”
Section: Innate Immune Responses To Rsvmentioning
confidence: 99%